Heavy metal accumulation in a bioindicator species, Limpet Patella caerulea, in Yalova (İzmit Bay): Risk assessment for human health - Çulha Saniye Türk; Dalkıran Görkem; Horzum Nesrin (Oceanological and Hydrobiological Studies, 2022)
In this study, monthly heavy metal concentrations in the whole-body tissue of Patella caerulea (Mediterranean limpets), a bioindicator species living in the coastal zone of the Gulf of Izmit (Marmara Sea), were examined for the first time. The mean metal concentrations in Patella caerulea (mg kg−1 dw) were 2.01–5.74 Cd, 2.45–12.90 Cu, 0.74–1.95 Pb, 21.12–109.57 Zn, 16.31–154.67 Ni, and 1120.67–3086.00 Fe. Cd levels in all months and Pb levels in October and November were found to be above the safe limits set by international organizations. The estimated daily intakes and estimated weekly intakes determined for each heavy metal were below the acceptable daily intakes and provisional tolerable weekly intakes. However, the target hazard quotient and total target hazard quotient values calculated for Cd, Ni, and Fe were found to be higher than 1. The carcinogenic risk value was also found to be high.